Press Code: A Shoulder Surfing Resistant Authentication Scheme for Smart Devices - Nur Nadiah Hanim, Mohd Nor (2016)
A memorization-based locking system is widely used in today’s smart devices, where a user has to repeat a text/number/pattern/others from the remembrance that has been registered before. He/she would be allowed to access the device if the newly given password is matched with the registered one. However, among this class of passwords, graphical password schemes are more compatible for smart devices due to their heavily graphic-oriented nature. However, existing graphical password schemes experience various attacks and threats. Among them shoulder surfing is the most prominent one, where an attacker can observe the password through picking on the screen. In this project, we propose a shoulder surfing resistant password scheme using press code, which is a new kind of code; and hence, a novel authentication scheme. In the proposed technique, a user can authenticate thyself by repeating the registered press code. We implement our proposed technique on the Android platform, and we have a prototype to demonstrate at present.